Experimental investigation of solar steam generator using nanocoating. (2020) - Uthirapathy, C.; Swaminathan, G.; Mathivanan, A.; Kumar, S.D.; Manikandan, G.; Madhesh, D.
Abstract: Concentrated solar power generation has become one of the most efficiently used solar energy conversion technologies in the modern world. The solar receiver or the reflector plays a major role in both the conventional concentrated steam generation process and in our proposed project too; in short, its performance can directly affect the overall efficiency of the system. In addition to the conventional concentrating dish, the research work will also propose a new design. The novelty of the work is introduces a new design for the core in such a way that it is a combination of the conventional solar sterling cycle and the helical heat exchangers, thus will increases the amount of heat that is being transferred onto the core and in turn increasing the amount of heat being transferred to the inlet water. Further the copper core is coated with the TiO2 Nano-particles to increase the ability to withstand high temperature and also because of their photo- catalytic properties they have the ability to retain the heat that it is being very much required to increase the temperature. Then the entire setup is experimentally investigated with vacuum environment and non vacuum environment. The vacuum with nano coated core produces the maximum temperature in the conversion of water in to steam compare to non coated core without vacuum.